PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN - Dini Anggraini Siregar; Susilawati (CV. ADIBA AISHA AMIRA, 2022)
Occupational safety and health are important factors in the work environment that can affect work motivation and employee performance. When employees work in safe and healthy conditions, they tend to have higher motivation to do a good job. A safe and risk-free work environment can provide employees with a sense of security and protection, so they can focus on their tasks better. The purpose of this study is to analyze the relationship between occupational safety and health and work motivation in an organizational context. The research method used in writing this journal is to use a literature review approach. with the inclusion criteria, namely, journals published in the last 10 years and samples in the study were obtained through Google Scholar, Scopus, and Sinta